A 90-year record of glacier changes in the Novaya Zemlya Archipelago, Russian High Arctic - Maraldo, Dean R.; Choi, Woonsup (Polar research, 2025)
Glacial retreat in the Russian High Arctic, particularly in the Novaya Zemlya Archipelago (NZA), is emblematic of global warming. Some global models project that, by 2100, sea-level rise contributions from melting glaciers in this region could be comparable to contributions from Antarctica’s and Greenland’s peripheral glaciers. However, historical glacier change in the NZA remains poorly known. Here, we present the longest decadal chronology of glacier change in the NZA to date, including a 90-year record (ca. 1931–2021) of frontal length change, and a 70-year record (1952–2021) of glacier area change. Using a combination of survey records, historical maps and satellite imagery, we analyse changes for 63 outlet glaciers, representing 86% of the NZA’s total ice mass. Our results show that the average frontal retreat rate increased each decade since the early 1970s, reaching a peak retreat rate of 65 m a-1 between 2011 and 2021. Glaciers terminating in the Barents Sea experienced the greatest losses, retreating an average of 4.2 km (11.6%) since 1952. During this time, the total glacier area decreased by 1606 km2 (10%). We identified increasing summer air and sea-surface temperatures as key drivers of accelerated glacier retreat, with peak air and sea-surface temperatures occurring from 2011 to 2021, corresponding to the period with the fastest retreat rates and the largest glacier area loss.